Peran Digital Marketing Berbasis Media Sosial Untuk Meningkatkan Volume Penjualan dan Mencapai Keberhasilan Usaha - Rusmalia, Nenda; Ratumbuysang, Monry Fraick Nicky Gillian; Setiawan, Ananda; Supriyanto, Supriyanto (Universitas Negeri Surabaya, 2024)
This study aims to analyse the effect of social media-based digital marketing on increasing sales volume and business success of MSMEs in Banjarbaru City. The problem is focused on the high failure rate experienced by MSMEs, so efforts are needed to increase the sales volume of MSMEs through social media-based digital marketing and achieve business success. The research method used is descriptive research with a quantitative approach. The sample was taken using purposive sampling technique as many as 168 MSME players in Banjarbaru City. Data collection techniques through observation, interviews and questionnaires to MSME actors and by taking references from journals, books and other relevant sources. Data analysis in this study was carried out using descriptive statistical analysis, path analysis, classical assumption analysis, simple regression analysis and partial test (t-test). The results showed that there is a positive influence between social media-based digital marketing on sales volume and business success of MSMEs in Banjarbaru City.